HOW PLATFORM FEATURES DRIVE CONSUMER BEHAVIOR ON OMNICHANNEL IN INDONESIA - Sinta Rukiastiandari; Dede Suleman; Lilik Yuliawati; Fara Mutia; Luthfia Rohimah; Aprillia (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2023)
This study investigates the relationship between platform features, customer engagement, satisfaction, purchase and repurchase intentions, and customer types in omnichannel retail. A survey of 250 participants utilized an online questionnaire, analyzed with statistical methods. Results show that platform convenience and advanced features drive satisfaction, purchase, and repurchase intentions. Impact on customer engagement varies by customer type. Ease of use indirectly affects satisfaction, purchase, and repurchase via engagement and customer type. The research underscores considering customer type when assessing ease of use and design impact on outcomes. It reveals intricate relationships, surpassing prior research by illustrating how platform features affect diverse customer engagement. Ease of use indirectly influences loyalty via engagement and customer type. This underscores a multifaceted loyalty formation. Businesses must factor engagement and customer type in platform refinement for target audience needs. Study underscores understanding platform features, engagement, and loyalty interplay for enhanced customer experiences and business success. It establishes a foundation for future research and practical omnichannel retail improvements.